Model Peningkatan Kinerja Operasional melalui Praktek-praktek Manajemen Kualitas Pada Industri Kecil Menengah (IKM) di Kota Semarang - Marno Nugroho (Conference In Business, Accounting, And Management (CBAM), 2015)
Studies on quality management at the moment is still very relevant to be discussed and followed up with research along with the development activities of the manufacturing industry, especially in Indonesia as one of the countries in South East Asia which is the purpose of industrial activity in the future, since this area is referred to as a cheaper production house of which 70% from industrial activities will be focused in the Southeast Asia region. One of the biggest obstacles experienced by the organization in implementing total quality culture is an obstacle. Every organization in doing the job as achieving total quality commitment will involve employees inÂ all aspects of planning and implementation, to ensure the provision of skills training of employees, and the achievement of organizational goals. The population in this study were all manufacturing companies in the city of Semarang which generally have a competitive advantage through a commitment to quality management peningatan. The approach used is descriptive analytical to determine the influence of environmental management on environmental performance and the performance of the company. To examine the influence of the independent variables, the dependent variable, and the culture of quality used regression test interaction. The analysis showed that the quality management influence either directly or moderated by a culture of quality in SMEs in Semarang with numbers sig <0.05. While partially can be analyzed most dimensions of quality management and quality culture failed to affect operational performance. Â Keywords: operational performance, quality management, quality culture, SMEs, sustainability